Nitrate and nitrite acute poisoning in feedlot cattle caused by ingestion of Portulaca oleracea - Sosa, Emiliano; Azaldegui, Ignacio; Barale, Joaquin; Sainz Rozas, Hernan Rene; Scioli, Maria Valeria; Poo, Juan Ignacio; Lauro, Adriana Araceli; Ovelar, María Florencia; Pachiani, Martina; Garcia, Juan Agustin; Canton, German Jose (Springer, 2025)
Nitrate and nitrite poisoning is a frequently lethal disease diagnosed in production animals due to the consumption of excessive levels in feed or water. The aim of this report was to describe an acute outbreak of nitrate and nitrite poisoning in two feedlot pens, affecting 17.5% and 5.7% of 8-month-old calves, respectively, due to the consumption of Portulaca oleracea (“purslane”) present in the pen. No gross or histopathological findings were observed during post-mortem examination and abundant Portulaca oleracea stems were observed in the reticulo-ruminal content. High levels of nitrate were detected in P. oleracea from pens where calves died. Although nitrate poisoning is widely reported after the consumption of different forage under certain environmental situations, some weeds can accumulate potential lethal nitrate levels.